2023
DOI: 10.1161/atvbaha.122.317781
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemic Dysregulation of Calpain in Lymphatic Endothelial Cells Interferes With Regulatory T-Cell Stability and Trafficking

Abstract: Background: Although hypercholesterolemia reportedly counteracts lymphocyte trafficking across lymphatic vessels, the roles of lymphatic endothelial cells (LECs) in the lymphocyte regulations remain unclear. Previous studies showed that calpain—an intracellular modulatory protease—interferes with leukocyte dynamics in the blood microcirculation and is associated with hypercholesterolemic dysfunction in vascular endothelial cells. Methods: This study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Qingkang Lyu, Klaus Ley I n this issue of Arteriosclerosis, Thrombosis, and Vascular Biology, Miyazaki et al 1 investigated the role of calpain in regulatory T lymphocyte stability and trafficking under hypercholesterolemia. The authors demonstrated that lysophosphatidic acid (LPA) induced overexpression of calpain in lymphatic endothelial cells (LECs).…”
Section: How Lymphatic Endothelial Cells Destabilize Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qingkang Lyu, Klaus Ley I n this issue of Arteriosclerosis, Thrombosis, and Vascular Biology, Miyazaki et al 1 investigated the role of calpain in regulatory T lymphocyte stability and trafficking under hypercholesterolemia. The authors demonstrated that lysophosphatidic acid (LPA) induced overexpression of calpain in lymphatic endothelial cells (LECs).…”
Section: How Lymphatic Endothelial Cells Destabilize Regulatory T Cellsmentioning
confidence: 99%
“…Furthermore, Miyazaki et al 1 explored a possible causative relationship of calpain activation in atherosclerosis. The authors first showed that calpastatin expression was reduced in LECs in hypercholesterolemic mice.…”
mentioning
confidence: 99%
“…Miyazaki et al [26 ▪▪ ] studied the calpain systems in lymphatic endothelial cells (LECs). Calpains are a family of Ca 2+ -dependent, nonlysosomal proteases [27 ▪ ].…”
Section: Lysophosphatidic Acid In Lymphatic Endothelial Cellsmentioning
confidence: 99%
“…Activated calpains can selectively degrade the inhibitor of κB (IκB) causing the activation of NFκB [27 ▪ ]. In vitro , Miyazaki et al [26 ▪▪ ] demonstrated that LPA downregulated calpastatin and upregulated calpain 2 in lymph node-derived murine endothelial cells that have the majority of LEC markers and properties (SVEC4-10 cells) [26 ▪▪ ]. In cocultures of SVEC4-10 cells and CD4 + T cells, it was found that knocking down the calpain-s1 gene ( Capns1 ), which encodes a common regulatory subunit of conventional calpains, expanded Foxp3+ Tregs, and in the presence of LPA, upregulated Treg-associated cytokines IL-10 and TGF-β1 [26 ▪▪ ].…”
Section: Lysophosphatidic Acid In Lymphatic Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation